2021
DOI: 10.1007/s11669-021-00902-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Multiples as a Tool to Efficiently Explore the Composition Space of High Entropy Alloys

Abstract: The concept of high entropy alloys (HEAs) has already provided specific alloys presenting improved structural and functional properties. However, the discovery and development of new HEAs still represent a big challenge due to their chemical complexity. Diffusion multiples can be used as an experimental approach to screen large composition ranges. The method consists in heat-treating intimately bonded metallic blocks to activate diffusion, thus creating gradients of compositions. Local chemical and physical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…These types of multidimensional datasets are increasingly being used for the characterization of microstructurally heterogeneous MPEAs. [17][18][19][20][21][22][23] For example, Coury et al recently performed high-throughput nanoindentations on a compositionally-graded sample in the CoCrFeNiMn HEA system [20] and found a good correlation between experimental results and predicted solid solution strengthening represented by atomic size mismatch. The authors highlighted the potential of high-throughput nanoindentation mapping of samples with controlled chemical gradients for fast screening of a vast multicomponent space.…”
Section: Doi: 101002/adem202300110mentioning
confidence: 99%
See 2 more Smart Citations
“…These types of multidimensional datasets are increasingly being used for the characterization of microstructurally heterogeneous MPEAs. [17][18][19][20][21][22][23] For example, Coury et al recently performed high-throughput nanoindentations on a compositionally-graded sample in the CoCrFeNiMn HEA system [20] and found a good correlation between experimental results and predicted solid solution strengthening represented by atomic size mismatch. The authors highlighted the potential of high-throughput nanoindentation mapping of samples with controlled chemical gradients for fast screening of a vast multicomponent space.…”
Section: Doi: 101002/adem202300110mentioning
confidence: 99%
“…The sample, extensively investigated in a previous work, [12] is structurally homogeneous (fcc) but exhibits a typical dendritic-interdendritic microstructure with segregation of Cr in the interdendritic region. As solid solution strengthening in HEAs can lead to remarkable increases in hardness and is strongly dependent on the chemical composition, [20,21,33] it was hypothesized that the observed microsegregation would be reflected in high-throughput nanohardness maps and that statistical elaboration of the measurement output would be useful in determining the individual mechanical properties of the specific phases. It will be shown that the accuracy of this type of measurement is highly influenced by the metallographic preparation procedure (chemical-mechanical polishing, electropolishing) and that the ISE of this alloy is important up to depths largely exceeding those normally used for high-resolution indentation mapping.…”
Section: Doi: 101002/adem202300110mentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion couples and multiples consist of two or more specimens of different compositions in contact with each other. [14,28,29] A diffusion heat treatment creates a composition profile by interdiffusion and provides a much larger characterization volume compared to thin films. Such material libraries have effectively been used to investigate phase stabilities and microstructures for the determination of phase diagrams.…”
Section: Introductionmentioning
confidence: 99%